RNA sequencing least shrew (Cryptotis parva) brainstem and gut transcripts following administration of a selective substance P neurokinin NK1 receptor agonist and antagonist expands genomics resources for emesis research - Irizarry, Kristopher J. L.; Zhong, Weixia; Sun, Yina; Kronmiller, Brent A.; Darmani, Nissar A. (Frontiers in Genetics, 2023)
The least shrew is among the subset of animals that are capable of vomiting and therefore serves as a valuable research model for investigating the biochemistry, molecular biology, pharmacology, and genomics of emesis. Both nausea and vomiting are associated with a variety of illnesses (bacterial/viral infections, bulimia, exposure to toxins, gall bladder disease), conditions (pregnancy, motion sickness, emotional stress, overeating) and reactions to drugs (chemotherapeutics, opiates). The severe discomfort and intense fear associated with the stressful symptoms of nausea and emesis are the major reason for patient non-compliance when being treated with cancer chemotherapeutics. Increased understanding of the physiology, pharmacology and pathophysiology underlying vomiting and nausea can accelerate progress for developing new antiemetics. As a major animal model for emesis, expanding genomic knowledge associated with emesis in the least shrew will further enhance the laboratory utility of this model. A key question is which genes mediate emesis, and are they expressed in response to emetics/antiemetics. To elucidate the mediators of emesis, in particular emetic receptors, their downstream signaling pathways, as well as the shared emetic signals, we carried out an RNA sequencing study focused on the central and peripheral emetic loci, the brainstem and gut. Thus, we sequenced RNA extracted from brainstem and gut tissues from different groups of least shrews treated with either a neurokinin NK1 receptor selective emetic agonist, GR73632 (5 mg/kg, i.p.), its corresponding selective antagonist netupitant (5 mg/kg, i.p.), a combination of these two agents, versus their corresponding vehicle-pretreated controls and drug naïve animals. The resulting sequences were processed using a de-novo transcriptome assembly and used it to identify orthologs within human, dog, mouse, and ferret gene sets. We compared the least shrew to human and a veterinary species (dog) that may be treated with vomit-inducing chemotherapeutics, and the ferret, another well-established model organism for emesis research. The mouse was included because it does not vomit. In total, we identified a final set of 16,720 least shrew orthologs. We employed comparative genomics analyses as well as gene ontology enrichment, KEGG pathway enrichment and phenotype enrichment to better understand the molecular biology of genes implicated in vomiting.